2002
DOI: 10.1039/b109748b
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the chemical stability of arsenosugars in simulated gastric juice and acidic environments using IC-ICP-MS and IC-ESI-MS/MS© US Government.

Abstract: A more quantitative extraction of arsenic-containing compounds from seafood matrices is essential in developing better dietary exposure estimates. More quantitative extraction often implies a more chemically aggressive set of extraction conditions. However, these conditions may result in undesirable chemical changes in the native arsenicals which may further complicate the toxicological risk assessment. This balance between quantitative extraction and species-specific integrity may be best addressed by using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 11 publications
2
75
1
Order By: Relevance
“…flagelliforme) powder was shown to contain an arsenosugar (oxo-arsenosugar-glycerol, Oxo-Gly), [26] this has not been demonstrated in isolated species [25] or axenic cultures of Nostoc. Although Yin et al [10] demonstrated As methylation by an arsM gene product in cyanobacteria including Synechocystis and Nostoc, they have not yet investigated arsenosugar production (because their aim was to check methylated species, only samples prepared by HNO 3 and microwave treatments, in which sugars might not be preserved, [28] were analysed). If it is substantiated that cyanobacteria have a mechanism to produce arsenosugars, their new role in the natural cycling of As in the environment as a source of arsenosugars will be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…flagelliforme) powder was shown to contain an arsenosugar (oxo-arsenosugar-glycerol, Oxo-Gly), [26] this has not been demonstrated in isolated species [25] or axenic cultures of Nostoc. Although Yin et al [10] demonstrated As methylation by an arsM gene product in cyanobacteria including Synechocystis and Nostoc, they have not yet investigated arsenosugar production (because their aim was to check methylated species, only samples prepared by HNO 3 and microwave treatments, in which sugars might not be preserved, [28] were analysed). If it is substantiated that cyanobacteria have a mechanism to produce arsenosugars, their new role in the natural cycling of As in the environment as a source of arsenosugars will be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Gamble et al 32) reported that AsSug 408 and AsSug 482 were degraded to DMA via AsSug 328 in a basic environment. In acidic conditions, the formation of AsSug 254 26) and an increase in DMA with heating 33) were also reported. Both of our Boso hijiki products (#6 and #7) contained DMA at the concentration of 0.8 µg/kg dw hijiki, while the DMA levels in two raw hijiki samples (#8 and #9) were much lower (0.2 µg/kg dw hijiki), and these changes in DMA amount may be enhanced by heating.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of AsSug 391 in Hijiki fusiforme was reported by Edmonds et al 10) Formation of AsSug 254 from AsSugs 328, 392, 408 and 482 in acidic environments has been reported. 26) Even though AsBe was recently detected in six kinds of marine algae, 27) its contamination from epifauna should be examined more carefully. Therefore, further study is necessary to confirm the existence of AsSug 254 and AsBe in hijiki seaweed.…”
Section: Discussionmentioning
confidence: 99%
“…[31] In the present study, Gly-riboside and PO 4 -riboside were the major arsenoribosides found in animal tissues (Tables A6 and A8). As the animals' digestive systems are mainly alkaline to neutral and not likely to experience low pH for long periods, degradation of arsenoribosides to OH-riboside, shown to occur slowly at low pH, [9,45] would probably not occur in these organisms.…”
Section: Possible Mechanisms For the Metabolism Of Arsenoribosides Anmentioning
confidence: 99%
“…[4,5] Thioarsenoribosides have also been found in molluscs. [6][7][8] At low pH (∼1), arsenoribosides degrade to 5-dimethylarsinoyl-α/β-ribofuranose (OH-riboside) [9] whereas at high pH (∼11), they are stable. [10] Anaerobic decomposition of arsenoribosides produces 2-dimethylarsinoyl ethanol (Me 2 As(O)-CH 2 -CH 2 OH; DMAE), [11] whereas aerobic decomposition produces OH-riboside, dimethylarsinate (DMA) and inorganic arsenic.…”
Section: Introductionmentioning
confidence: 99%